The secrets you keep ebook A novel. - White, Kate (2017)
From the New York Times bestselling author of The Wrong Man and Eyes on You comes a harrowing new psychological thriller about a successful self-help author who suddenly finds her life spiraling dangerously out of control. What would you do if you realized that your new husband, a man you adore, is keeping secrets from you—secrets with terrifying consequences? Bryn Harper, an accomplished self-help author, already has plenty to deal with. She's still recovering from a devastating car accident that has left her haunted by recurring, smoke-filled nightmares. Worse still, she can't shake the ominous feeling her dreams contain a warning. At the beginning of their relationship, Bryn's husband Guy couldn't have been more supportive. But after they move into a new house together, disturbing incidents occur and Guy grows evasive. Bryn is increasingly unsettled, and then a woman hired to cater their dinner party is brutally murdered. As Bryn's world unravels—and yet another woman in town is slain —she must summon her old strength to find answers and protect her own life. Her nightmares may in fact hold the key to unlocking the truth and unmasking the murderer. With unexpected, riveting twists, The Secrets You Keep is an utterly compelling psychological thriller that once again showcases Kate White's extraordinary storytelling talent.